Factors affecting buyers perceptions in accordance with marketing strategy: a case of vernacular Thai product - Sarath Simsiri; Nopadon Sahachaisaeree (My University, 2010)
Traditionally and locally made handicrafts such as Thai silk, pottery and wood carving are considered part of products with vernacular style. Development of such products need careful considerations, consumer discernment and aesthetic perceptions are among crucial factors determining the success of the design, and therefore, determining the acceptance of the products. The research uses a set of vernacular design as case study to test the cognitive perception of prospective users—between those who discern and not-discern the history of utensils. Distinctive consumers—tourists from oversea, local folks, and urbanites—are controlled variables assumed to post different tastes and perceptions.
Keywords: Discernment; Handicraft; Cultural Industries and Urban Development